Arthroscopic Posteromedial Capsular Release - Dean, Chase S. (Arthrosc Tech, 2016)
Post-traumatic or postsurgical flexion contractures of the knee can significantly limit function and lead to gait abnormalities. In this setting, interventions to regain full extension may include bracing, physical therapy, and open or arthroscopic surgery. Open surgical approaches to restore full motion often demand extensive recovery and promote further adhesions and loss of motion, which has led to the advent of arthroscopic techniques to address these pathologies. We present a safe, effective, and reproducible arthroscopic technique for posteromedial capsular release to address knee flexion contractures.